Analisis Tingkat Penerapan Perhitungan Struktur Pada Pembangunan Rumah Sederhana - Zebua, Dermawan; Giawa, Jun Fajar Krisman (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2025)
The construction of simple houses is one of the solutions to provide housing for low-income communities in Indonesia. However, the application of structural calculations in the construction process is often overlooked, posing risks to the quality and safety of buildings. This study aims to analyze the level of implementation of structural calculations in the construction of simple houses, identify the influencing factors, and provide recommendations to improve their application. The research employed a descriptive quantitative method by collecting data through field observations, interviews, and document reviews of 50 simple house units in both urban and rural areas. The results show that the average application rate of structural calculations is only 37.6%, with the highest implementation in foundation components (46%) and the lowest in floor slabs (28%). The main inhibiting factors include economic considerations, lack of technical awareness, limited availability of professionals, and minimal government supervision. Houses built without structural calculations are more vulnerable to damage such as wall cracks, foundation settlement, and roof frame deflection. This study recommends enhancing public awareness, providing affordable design services, involving universities, and strengthening regulations to improve the construction quality of simple houses in Indonesia.